Diversity of Termite (Insecta: Isoptera) at the Forested Area of Universitas Andalas, Padang, West Sumatra, Indonesia. Issue 1 (1st July 2022) - Mairawita,; Herwina, H; Rahman, T; Janra, M N
Abstract: The termites are ubiquitous whenever their food available. Hence, they can be found almost in every place where woods or wooden structure exist. This research intended to do the inventory on termite (Isoptera) diversity at the Biological Education and Research Forest (BERF), Medicinal Plant Garden and Animal Husbandry Faculty's Field Station; all of them are forested parts of Universitas Andalas in Limau Manis Padang, West Sumatra. These forested sections of the campus area have purposes for maintaining some ecological functions as well as to become site where the practice of research and education implemented. The research had been conducted from March to July 2020. Termites were sampled along the transect using direct collecting method. As result, it was recorded a total of 12 species belonged to nine genera, four subfamilies and two families. Termitidae had the highest records with 11 species identified, while Rhinotermitidae was termite family with only one species recorded. Nasutitermitinae, with seven species, became subfamily with the most members found, followed by Termitinae with three species, Macrotermitinae and Rhinotermitinae with one species each. The forested area of Universitas Andalas had moderate termite diversity (H' = 2.08).